v.1 - "Bandler, Richard" (Palo Alto, 1975)
These seminal works in neurolinguistic programming (NLP) help therapists understand how people create inner models of the world to represent their experience and guide their behavior. Volume I describes the Meta Model, a framework for comprehending the structure of language; Volume II applies NLP theory to nonverbal communication.
Keywords: Magic